1996
DOI: 10.1038/bjc.1996.56
|View full text |Cite
|
Sign up to set email alerts
|

The effects of beta-human chorionic gonadotrophin on the in vitro growth of bladder cancer cell lines

Abstract: Summary The effects of human chorionic gonadotrophin (hCG) and its subunits on in vitro bladder cancer cell growth have been assessed using the a tetrazolium salt reduction assay (MTT). Intact hCG, a-hCG and f,-core hCG all had no effect on cell growth, while fl-hCG increased MTT reduction in all four bladder cancer lines tested. The magnitude of ,B-hCG stimulation was maximal in the T24 line, which does not itself produce P-hCG and appeared to be correspondingly lower in ,B-hCG-secreting lines. The addition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
2

Year Published

1998
1998
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 20 publications
(11 reference statements)
3
70
0
2
Order By: Relevance
“…It is now apparent that this event may significantly affect tumour development given the growth effects recently described (LunardiIskander et al, 1995;Gillott et al, 1996). It is accepted that free hCGβ is unable to activate the LH/hCG receptor and stimulate the subsequent second messengers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is now apparent that this event may significantly affect tumour development given the growth effects recently described (LunardiIskander et al, 1995;Gillott et al, 1996). It is accepted that free hCGβ is unable to activate the LH/hCG receptor and stimulate the subsequent second messengers.…”
Section: Discussionmentioning
confidence: 99%
“…T24 has been shown to be the most sensitive to the addition of hCGβ believed to be due to the fact that it produces no endogenous hCGβ of its own (Gillott et al, 1996). SCaBER and RT112 are high level hCGβ producers and 5637 and J82 low level hCGβ producers (Iles and Chard, 1989).…”
Section: Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…hCG␤ has been shown to exert a growth-promoting effect in culture, 27 and in bladder cancer cells, this has been shown to result from inhibition of apoptosis. 28 No receptor for hCG␤ has been identified, but based on the structural similarity between hCG␤ and the so-called cysteine-knot growth factors, 29 eg, transforming growth factor ␤, platelet-derived growth factor-B, and nerve growth factor, it has been suggested that hCG␤ interferes with the growth-inhibiting effect of these through a paracrine or autocrine route.…”
Section: Hcg␤ In Renal Cellmentioning
confidence: 99%
“…However, it has now been shown that the -subunit may have its own unique functions. Lunardi-Iskandar et al (1995) and Gillott et al (1996) have shown growth inhibitory and growth stimulatory effects respectively of free hCG . Recently, elucidation of the crystal structure of hCG revealed a similar topology between hCG and transforming growth factor (TGF ), platelet derived growth factor (PDGF ) and nerve cell growth factor (NGF) (Lapthorn et al 1994, Wu et al 1994.…”
Section: Introductionmentioning
confidence: 99%